DISTRIBUSI WAKTU ANTAR KEDATANGAN PENUMPANG TRANSMETRO BANDUNG RUTE CICAHEUM-CIBEUREUM - Stefani, Fransiska; Joewono, Tri Basuki (FSTPT Indonesia, 2015)
The level of a bus service system is affected by several factors, namely the frequency of bus arrival and the rate of passenger arrival time among others. The passenger arrival time is affected by passengers’ knowledge of bus schedule. The purpose of this study is to analyze the pattern of distribution of passengers arrival time at bus shelters located in the corridor Cicaheum-Cibeureum and to determine the suitable probability distribution. The result of analysis showed that passengers arrival time follows Weibull distribution based on one week data with an average value 1,75 minutes. The analysis also indicated that passengers arrival time on each category of bus headway compatible with Weibull distribution with average value between 1,28 minutes and 3,06 minutes.